2009
DOI: 10.1159/000241734
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Thiazolidinediones (Glitazones) with the ATP-Binding Cassette Transporters P-Glycoprotein and Breast Cancer Resistance Protein

Abstract: Aims: Thiazolidinediones (glitazones) are frequently prescribed antidiabetic drugs commonly used in combination drug regimens. To evaluate the risk of drug-drug interactions, we therefore aimed to systematically investigate the inhibitory and inductive effects of all glitazones on 2 of the most relevant drug transporters, P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP), in vitro. Methods: The inhibition of P-gp and BCRP was assessed by fluorometric assays quantifying the increase in the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 88 publications
1
14
0
Order By: Relevance
“…Abcc1, 2, 4, and Abcg2 mRNA and/or protein expression was increased in liver, which is consistent with what was observed in livers of T2DM rats [49]. Abcc1 and Abcg2, along with Abcb1, can transport the antidiabetic drug rosiglitazone [50]. Severe liver injury has been reported in a person with T2DM [51] and cholestatic injury has also been observed after rosiglitazone therapy [52] – both suggesting hepatic clearance is necessary.…”
Section: Discussionsupporting
confidence: 74%
“…Abcc1, 2, 4, and Abcg2 mRNA and/or protein expression was increased in liver, which is consistent with what was observed in livers of T2DM rats [49]. Abcc1 and Abcg2, along with Abcb1, can transport the antidiabetic drug rosiglitazone [50]. Severe liver injury has been reported in a person with T2DM [51] and cholestatic injury has also been observed after rosiglitazone therapy [52] – both suggesting hepatic clearance is necessary.…”
Section: Discussionsupporting
confidence: 74%
“…Our findings are comparable to another study that investigated the involvement of transporters at the human placental apical membrane on the penetration of rosiglitazone, a close structural analogue of pioglitazone. Having investigated effects of three drug efflux transporters (P-gp, BCRP and Multidrug Resistance Protein, MRP1) at the human placental apical membrane, Weiss et al also found that rosiglitazone was predominantly transported by P-gp24. We noted a small rise from 16.92 to 20.82% in the brain-plasma ratios after treatment with the P-gp inhibitor or P-gp + BCRP inhibitors.…”
Section: Discussionmentioning
confidence: 56%
“…At present, no study has successfully addressed this factor. Therefore, in this study, we investigated the two most relevant drug efflux transporters, P-gp and breast cancer resistance protein (BCRP)24, as potential barriers to brain penetration of pioglitazone. Our in vivo experiments demonstrate that inhibition of P-gp leads to a significant although not substantial increase in the levels of pioglitazone in brain tissue, indicating the involvement of P-gp in limiting pioglitazone brain penetration.…”
mentioning
confidence: 99%
“…The function of AMPK in regulating glucose metabolism has been demonstrated with several AMPK activators, such as metformin and AICAR, to increase AMPKa phosphorylation and mediates glucose metabolisms both in vivo and in vitro 9, 10 . Thiazolidinedione (TZDs) up-regulates the cellular AMP/ATP ratio, which in turn activates AMPK activation and suppresses gluconeogenesis 11 .…”
Section: Introductionmentioning
confidence: 99%